RENEWAL OF ISLAMIC THOUGHT - Sajadi, Darun (Spektra: Jurnal Ilmu-ilmu Sosial, 2019)
There are two factors that create the issue of renewal in Islam, precisely the renewal of understanding of Islam, both actual and controversial throughout the history of Islamic thought. Both of these factors are intrinsic, inherent in Islam itself, and therefore can be seen as the character of Islam. First, the Islamic universal character. This character requires a new understanding to respond to the ever-changing development of human life. Universal Islam, in the sense that it is suitable for all space and time (shâlih li-kulli zamân wa makân), demands the actualization of Islamic values in the context of cultural dynamics. This contextualization is an attempt to discover the relationship between the Islamic nature and the spirit of the times. The essence of Islam, the dignity and universality, are related to the spirit of times; which is a tendency to renewal and progress. The achievement of the ideals benefit for all really depends on new discoveries of methods and techniques for a better and more advanced life. Second, the absoluteness of Islamic character. That is as a religion that is believed by its followers as absolute truth. This belief has the implication that Islam is a system that solves other systems, and even Islam is the only valid system while the other is inappropriate. These two characteristics of Islam, universality and absoluteness, each have their basis in the Holy Qur’an. Renewal in Islam is actually a rationalization of Islamic understanding and contextualization of Islamic values into life. Rationalization implies an effort to find the substance and removal of symbols. Whereas contextualization implies an effort to correlate the substance with a specific socio-cultural platform and the possibility of using these cultural symbols to repackage the substance itself. Rationalization and contextualization can be referred to as the process of interpretation of Islam into the cultural process, and the allocation of these values into new cultures. Renewal in Islam involves a substantive approach (emphasizing content) on Islam. This is what distinguishes between reformers and their critics who tend to maintain a formalistic approach in understanding and applying Islamic theory.